2018
DOI: 10.1038/s41419-018-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts induce PDL1+ neutrophils through the IL6-STAT3 pathway that foster immune suppression in hepatocellular carcinoma

Abstract: Emerging evidence indicate that cancer-associated fibroblasts (CAFs) affect tumor progression by reshaping the tumor microenvironment. Neutrophils are prominent components of solid tumors and important in cancer progression. Whether the phenotype and function of neutrophils in hepatocellular carcinoma (HCC) are influenced by CAFs is not well understood. Herein, we investigated the effect of HCC-derived CAFs (HCC-CAFs) on the neutrophils and explored the biological role of this effect. We found that HCC-CAFs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
244
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(271 citation statements)
references
References 31 publications
8
244
0
1
Order By: Relevance
“…Evidences have shown the vital role of CAFs in cancer evasion of the immune surveillance, including hepatocellular carcinoma (HCC), esophageal cancer, CRC and melanoma . It was reported that CAFs secreted cytokines, such as, IL‐6, IL‐4, IL‐8, IL‐10, tumor necrosis factor (TNF), TGF‐β, C‐C motif chemokine ligand 2 (CCL2), CCL5, C‐X‐C motif chemokine ligand CXCL9, CXCL10, CXCL12, have direct and/or indirect implications for tumor immunity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidences have shown the vital role of CAFs in cancer evasion of the immune surveillance, including hepatocellular carcinoma (HCC), esophageal cancer, CRC and melanoma . It was reported that CAFs secreted cytokines, such as, IL‐6, IL‐4, IL‐8, IL‐10, tumor necrosis factor (TNF), TGF‐β, C‐C motif chemokine ligand 2 (CCL2), CCL5, C‐X‐C motif chemokine ligand CXCL9, CXCL10, CXCL12, have direct and/or indirect implications for tumor immunity .…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that cytokines serve as mediators in shaping tumor microenvironment and facilitating tumor progression . Previous studies have reported that C‐X‐C motif chemokine ligand 12 (CXCL12), interferon‐γ (IFN‐γ), CXCL9/10/11 and IL6 promoted PD‐L1 expression in cancer cells . In this regard, we postulated that CAFs‐derived cytokines might promote PD‐L1 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has also revealed the role of HCC derived CAFs in fostering neutrophil mediated immune suppression in HCC. Specifically, HCC‐CAF derived IL‐6 was able to induce PD‐L1+ neutrophils via the JAK‐STAT3 pathway, which in turn impaired T cell function through PD‐1/PD‐L1 signalling and hence facilitated HCC progression …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tumor‐associated stromal cells/CAFs themselves also expressed PD‐L1 to suppress CD8 + antitumor immune responses in response to the inflammatory secretome from human colon cancer cells, and pre‐inflammatory cytokine TNFα and IL‐1β induced CXCL8/CCL5 secretion in the co‐culture of CAFs and triple negative breast cancers , suggesting that the inflammation also regulates the immunological response of CAFs/stromal cells in the TME. In addition, CAFs in HCC regulate the survival and activation of neutrophils through the IL‐6–signal transducer and activator of transcription (STAT) 3–PD‐L1 signaling pathway and consequently affect the function of T cells . Even after high‐dose irradiation, CAFs maintain their powerful immunosuppressive effect over activated T cells .…”
Section: Regulation Of Tumor Immune Response By Cancer‐associated Fibmentioning
confidence: 99%